Pitstop approach: diabetologist referral and quality of care in patients with type 2 diabetes – a Swiss longitudinal study - Fahim Ebrahimi; Simone Hubacher; Emanuel Christ; Stefan Zechmann (Swiss Medical Weekly)
STUDY AIMS: Patients with type 2 diabetes mellitus are typically managed in primary care settings, but management has become more complex in recent years due to modern therapeutic options. There is a paucity of data on the role of a one-off referral to an outpatient diabetes centre (a “pitstop” approach) in improving the quality of diabetes care.